Penerapan Arsitektur Neo Vernakular Pada Perancangan Sentra UMKM di Kabupaten Wonogiri Jawa Tengah - Fajar Setiawan; Tri Endangsih; Anggraeni Dyah Sulistiowati (MAESTRO, 2023)
UMKM (Micro, Small and Medium Enterprises) have an important role in regional and national economic growth, through their contribution to GDP. The number of Indonesian UMKM has increased every year, including UMKMs in Wonogiri. The existence of UMKM Centres in Wonogiri is motivated by the high potential of UMKM in Wonogiri and the lack of UMKM centre facilities in Wonogiri. To be able to improve the skills and creativity of UMKM, a container is needed as a means of developing marketing, training, coaching, and an integrated information system for UMKM from several scattered areas to become central. The UMKM Centre in Wonogiri Regency is designed in order to realise a building design that can increase competitiveness and be representative as a building to market local Wonogiri products. The application of neo vernacular architectural rules that are implemented on the scale of the building, the basic form and appearance of the building so as to create an atmosphere that does not leave the local character.